BRI as chance for regional cooperation: Iran - Armenia economic relations - Atom Margaryan; Emil Grigoryan; Armen Minassian (OrdnungsPolitisches Portal (OPO), 2022)
The Belt and Road Initiative is one of the platforms for regional cooperation that enables participating countries to develop and deepen economic ties. The South Caucasus has always had great historical, political, geographical and economic significance for Iran. Through the research, we tried to find out what is the level of infrastructure development of Armenia, Azerbaijan, Georgia, Türkiye and Iran, and what is the role of Iran in the trade of South Caucasus countries and Türkiye in 2002 and 2021. Armenia-Iran economic relations have been the closest. However, Armenia and Iran have not realized the full potential of cooperation. Providing a proper infrastructural base is one of the priority steps in that direction.
Keywords: 330; Silk Road Economic Belt; Economic Cooperation; Infrastructure; South Caucasus; Iran; Transit Hub; Economic Corridors